The Effect Of Storytelling Method On The Speaking Skills Of Third Graders: Pengaruh Metode Storytelling Terhadap Keterampilan Bebricara Siswa Kelas III - Maulidiyah Firda Yanti; Machful Indra Kurniawan (Universitas Muhammadiyah Sidoarjo, 2021)
The purpose of this study is to find how much the influence storytelling method for speaking skills of elementary school 01 Waru Sidoarjo inter class. The kind of the study use quantitative of kind pre-experimental with one grup desain of pretest-posttest. the sampling technique in this study use purposive sampling technique with certain considerations, which use all members of the population as a sample of 25 students inter A class. the data collection methods are descriptive statistic and analysis prerequisite tests and hypothesis testing. The results of students analysis are speaking skills before using the storytelling method is in the medium category. Furthermore, the T test was compare with a 5% significance level of 1.7081. Then it can be concluded that Ha was accepted and Ho was rejected. While the calculation of the level influence obtained 0,91 results which means that there is a large influence in the study, because eta square is 0,91 > 0,41. These results illustrate that the speaking skills of students in class 3 are influenced by using the storytelling method in grade 3 elementary school at Bangah 01 Waru Sidoarjo.